LANGUAGE PROFICIENCY AND CULTURAL AWARENESS: IMPACT OF BLACK LIVES MATTER IN EFL INSTRUCTION - Andrea Roxana BELLOT; Anca Daniela FRUMUSELU (Studia Universitatis Babeş-Bolyai. Philologia)
Language Proficiency and Cultural Awareness: Impact of Black Lives Matter in EFL Instruction. This paper evaluates the effectiveness of a Black Lives Matter (BLM) teaching unit designed to enhance students' cultural awareness and English as a Foreign Language (EFL) skills. Employing a mixed-method approach, the study investigates students' viewpoints through online questionnaires. The methodology integrates pre- and post-questionnaires to analyse the pedagogical impact, drawing on established theories of communicative competence and intercultural pedagogy to contextualize the study. The results demonstrate that the project significantly contributed to students' social consciousness development while also improving their English language proficiency.